(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
The Labor Reform introduced several changes to the Consolidation of Labor Laws (CLT), notably the increased flexibility to eliminate the intra-workday break. Given this change, this article analyzes the impacts of reducing the rest and meal break on workers’ health. The research adopted a qualitative approach, with exploratory and descriptive purposes, using bibliographic and documentary reviews as methodological procedures. The time frame covers the periods before and after the Labor Reform (Law No. 13,467/2017). The results demonstrate that the intra-workday break constitutes an important mechanism for limiting the workday, ensuring the protection of workers’ health and safety, as it is an institution aimed at restoring physical strength and preserving their mental health. Health impact assessment and the constitutional limitation of collective autonomy constitute relevant tools for mitigating harm and strengthening the protection of health and safety at work.